The Effect Of Competency, Job Satisfaction, And Work Motivation On Teacher Work Productivity At State High School (Man) 02 Merapi Timur Lahat Regency - Dita Dwi Kinanti; Titi Hasanah; Marko Ilpiyanto (Universitas Dehasen Bengkulu, 2026)
The purpose of this study was to determine the influence of competence, job satisfaction, and work motivation on teacher work productivity at State Islamic Senior High School (MAN) 02 Merapi Timur, Lahat Regency. The results of the study showed that (1) competence has a significant partial effect on work productivity, as evidenced by the calculated t value > t-table (2.192 > 2.005). (2) Job Satisfaction has a significant partial effect on Work Productivity, as shown by the calculated t value > t table (3.577 > 2.005). (3) Work Motivation has a significant partial effect on Work Productivity, as shown by the calculated t value > t table (4.399 > 2.005). (4) Competence, Job Satisfaction, and Work Motivation have a significant simultaneous effect on Work Productivity, as shown by the calculated f value > f table (18.124 > 4.020), with a significance value lower than the significance level (a) of 0.05 (0.000 < 0.05).